Religia w Republice Czeskiej na początku trzeciego tysiąclecia - Vaclavik, David (Space – Society – Economy, 2005)
Contrariwise the secularization thesis we think that the situation is more complicated even in such secular country as the Czech Republic is. Religion has not disappeared or will not disappear from political, social and cultural life. It has to be said that face of religion and religious life is changing. Because of these changes we are faced with religious pluralism, individualization of religious life and with something like "market competition" of many different religious groups and traditions. All of these changes are connected with the following factors - 1. There is high level of atheism in the Czech Republic, 2. There are big differences in affiliation to religion in regions of the Czech Republic, 3. There is big difference between proclamative declaration to some religious group or tradition and real identification with it, 4. Rate of affiliation to some religion, religious group or religious tradition depends on age. In the context of last mentioned factor we can say that youngest generation is more skeptical in face of traditional religious institution as established churches. Young people are more open for other religious and spiritual tradition without connection with some religious institutions. It is possible to say that typical representation of religious life of youngest Czech generation is unambiguously non-institutional and individual spirituality that combine different sorts of religious traditions and trends. We can divide contemporary religious scene in the Czech Republic into the three groups - 1. Traditional religious group, 2. New religious movements (NRMs) and 3. Individual and personal religiosity.